Una historia abreviada de la prensa satírica en España: desde El Duende Crítico de Madridhasta Gedeón - Llera Ruiz, José Antonio (Estudios sobre el Mensaje Periodístico, 2003)
Since the early 18th century underground political satire of El Duende Crítico de Madrid up to modern business journalism represented by Gedeón, Spanish satire magazines have gone trough several stages, even if, in general, its history is more related to the ideologization of their discourse and to invective than to the elegant examples by Clavijo y Farjardo or Larra during the Enlightenment.